Assessment of the Effectiveness of the Learning Interventions on the Job Performance of Selected Personnel of PRC Towards an Enhanced Learning Interventions - Quinicio, Ferdinand (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examines the relationship between learning interventions and employee performance among selected personnel of the Professional Regulation Commission (PRC) Central Office in Manila, Philippines. Grounded in Kirkpatrick’s Four-Level Training Evaluation Model, Human Capital Theory, and New Public Management (NPM) Theory, the research investigates how structured learning and development (L&D) programs influence key performance indicators including work quality, efficiency, teamwork and collaboration, and adaptability. A mixed-method research design was employed, combining a descriptive-correlational quantitative approach with qualitative insights from key informant interviews. Quantitative data were collected through a structured survey questionnaire administered to 171 PRC personnel who had participated in at least one learning intervention between 2022 and 2024, while qualitative data were obtained through interviews with five informants involved in training planning and implementation. Descriptive statistics and Pearson correlation analysis were used to analyze quantitative data, while thematic analysis was applied to qualitative responses. Findings revealed that PRC learning interventions received highly positive evaluations across reaction, learning, behavior, and results dimensions. Employees reported high levels of performance in work quality (M = 3.62), work efficiency (M = 3.58), teamwork and collaboration (M = 3.80), and adaptability (M = 3.60). Statistical analysis indicated a significant and moderately positive relationship between learning interventions and overall employee performance (r = 0.650, p = 0.0001), suggesting that structured training programs contribute to improved workplace competencies and productivity. Despite these positive outcomes, challenges such as limited resources, workload constraints, and the need for more strategic training planning were identified. The study recommends strengthening training evaluation systems, expanding digital skills and leadership development programs, and implementing post-training reinforcement mechanisms such as mentoring and coaching to sustain performance improvements. The study supports Sustainable Development Goal (SDG) 8: Decent Work and Economic Growth, SDG 16: Peace, Justice, and Strong Institutions, and SDG 4: Quality Education, as it highlights the importance of continuous professional development in strengthening workforce competence and improving institutional performance. By providing empirical evidence on the effectiveness of learning interventions in a government regulatory agency, the research contributes to institutional sustainability and public sector capacity-building, supporting evidence-based human resource development and improved public service delivery.
Keywords: Adaptability; Employee performance; Learning and development; Public sector training; Teamwork and collaboration; Work efficiency; Work quality